Increased NK Cell Maturation in Patients with Acute Myeloid Leukemia - Chretien, Anne-Sophie; Granjeaud, Samuel; Gondois-Rey, Françoise; Harbi, Samia; Orlanducci, Florence; Blaise, Didier; Vey, Norbert; Arnoulet, Christine; Fauriat, Cyril; Olive, Daniel (Frontiers in Immunology, 2015)
Understanding of immune alterations in cancer patients is a major challenge and requires precise phenotypic study of immune subsets. Improvement of knowledge regarding the biology of NK cells and the technical advances leads to the generation of high dimensional dataset. High dimensional flow cytometry requires tools adapted to complex dataset analyseis. This study presents an example of NK cell maturation analysis in Healthy Volunteers (HV) and patients with Acute Myeloid Leukemia (AML) with an automated procedure using the FLOCK algorithm. This procedure enabled to automatically identify NK cell subsets according to maturation profiles, with 2D mapping of a 4-dimensional dataset. Differences were highlighted in AML patients compared to HV, with an overall increase of NK maturation. Among patients, a strong heterogeneity in NK cell maturation defined three distinct profiles. Overall, automatic gating with FLOCK algorithm is a recent procedure which enables fast and reliable identification of cell populations from high dimensional cytometry data. Such tools are necessary for immune subsets characterization and standardization of data analyses. This tool is adapted to new immune cell subsets discovery, and may lead to a better knowledge of NK cell defects in cancer patients. This point is a cornerstone to develop therapeutic strategies based on NK cells. Overall, 2D mapping of NK maturation profiles enabled fast and reliable identification of NK cell subsets.